Symbolic Adoption Model of Local Government Management Information System - Suaryana, I Gusti Ngurah Agung; Noviari, Naniek; Damayanthi, I Gusti Ayu Eka (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022)DO - 10.24843/JIAB.2022.v17.i01.p06, 2021)
The purpose of this research is to create an acceptance model for the implementation of the Local Government Management Information System (LGMIS) financial application in the Denpasar City Government. In this study, the population consisted of all RAOs in the Denpasar City Government, a total of 36 RAOs and selected using saturated sampling methods and sampling of respondents was done by purposive sampling. SEM-PLS statistical analysis was used in this study. The findings of hypothesis testing show that information quality, system quality, management commitment, personal innovativeness, and computer self-efficacy have no effect on LGMIS's perceived usefulness. Personal innovativeness and computer self-efficacy have a positive effect on the perceived ease of use of the LGMIS. Ease of use has a positive effect on the financial LGMIS perceived usefulness. This study also proves that perceived ease of use and perceived usefulness have a positive effect on financial LGMIS symbolic adoption. Keywords:  regional management information system, technology acceptance model, symbolic adoption.